Family Empowerment Through Health Promotion in Managing Anemia and Chronic Energy Deficiency Among Pregnant Women in Labulia Village (Journal of Social And Education Research, 2025)
Anemia and chronic energy deficiency (CED) are common nutritional problems among pregnant women, adversely affecting maternal and fetal health. One effective strategy to address these issues is structured and targeted nutrition education. This study aimed to evaluate the effectiveness of a health education intervention in improving pregnant women’s knowledge regarding anemia and CED. The activity was conducted at Posyandu Anyelir, Labulia Village, involving 15 pregnant women. The method used included interactive lectures and group discussions. Participants’ knowledge was assessed through pretest and posttest evaluations. The results showed that before the education session, only 5 participants (33.3%) had good knowledge, which increased to 12 participants (80%) afterward. This significant improvement indicates that the applied educational methods were effective in enhancing understanding of anemia and CED prevention during pregnancy. In conclusion, the health education activity effectively increased pregnant women’s knowledge. It is recommended that similar programs be implemented sustainably in collaboration with relevant stakeholders to reduce the prevalence of anemia and CED in the community.